ANALISIS SISTEM INFORMASI AKUNTANSI ATAS SIKLUS PENGGAJIAN PADA PT â€œXâ€ DI SURABAYA - ASTRID ADIYANI, AYU (Jurnal Akuntansi AKUNESA, 2015)
This research are describes about implementation of the payroll systems on PT X. The purpose of this research is to understand the procedure of payroll systems and compare the procedure payroll systems with theory accounting information system of payroll. This research uses qualitative method with descriptive qualitative research approach. And the results indicate that the payroll system has been well implemented, it is shown by the separation of duties, authorization of transactions, and the responsibilities of each department. But needs additional department of general ledger, because it can help companies to recording payroll transaction process. Keyword: Accounting Information Systems, Payroll Systems